2018
DOI: 10.1044/2018_ajslp-17-0134
|View full text |Cite
|
Sign up to set email alerts
|

Speech Rate Entrainment in Children and Adults With and Without Autism Spectrum Disorder

Abstract: Findings suggest that speech rate entrainment is a developmentally acquired skill and offers preliminary evidence of speech rate entrainment deficits in adults with ASD. Impairments in this area may contribute to the conversational breakdowns and social difficulties experienced by this population. Future work is needed to advance this area of inquiry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 53 publications
(56 reference statements)
1
30
1
Order By: Relevance
“…These inconclusive findings across studies are not limited to young children. Similar discrepancies have been found in studies involving school-aged children and adolescents (Oviatt, Darves, & Coulston, 2004;Wynn, Borrie, & Sellers, 2018).…”
supporting
confidence: 82%
“…These inconclusive findings across studies are not limited to young children. Similar discrepancies have been found in studies involving school-aged children and adolescents (Oviatt, Darves, & Coulston, 2004;Wynn, Borrie, & Sellers, 2018).…”
supporting
confidence: 82%
“…Given the positive correlation between f0 entrainment and the success of conversations as well as personal and interpersonal attributes of the conversation partners ( Lubold et al, 2016 ; Michalsky and Schoormann, 2017 ; Michalsky et al, 2018 ; Niebuhr and Michalsky, 2019 ), the finding that children and teens with ASD show less mean f0 entrainment compared to their neurotypical peers is significant. Especially, seen that earlier studies on lexical and speech rate entrainment did not find differences between participants with and without ASD ( Nadig et al, 2015 ; Branigan et al, 2016 ; Hopkins et al, 2017 ; Wynn et al, 2018 ). Considering that deficits in social communication in those with ASD are considered a core-deficit in this population, measures of f0 entrainment behavior have the potential to serve as a biomarker for assessing both the presence and the severity of the social communication deficit in this population, and possibly in others with social communication deficits, directly.…”
Section: Discussionmentioning
confidence: 74%
“…However, Nadig et al (2015) report that while the participants with ASD were just as efficient as the controls, they were slightly slower and were less likely to incorporate the conversation partners’ contributions into their descriptions. Looking at prosodic entrainment behavior, Wynn et al (2018) investigated speaking rate in individuals with ASD—both children and adults—and found that only neurotypical adults exhibited entrainment in speech rate in their study. Wynn et al’s (2018) study was an important first step in the investigation of prosodic entrainment behaviors in those with ASD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As research in this area continues to grow, the adoption of a consistent system for organizing entrainment across research teams and studies would ensure greater cohesion and integration of knowledge. This is particularly true for speech-language pathology, a field where the need to rigorously measure and understand conversational phenomena is becoming increasingly recognized (see Barnes and Bloch, 2019) and research in conversational entrainment is starting to expand (e.g., Borrie et al, 2020a;Wynn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%